5‐Chloro‐2,4‐dihydroxypyridine, CDHP, prevents lung metastasis of basal‐like breast cancer cells by reducing nascent adhesion formation - Itou, Junji (Cancer Med, 2018)
A drug for metastasis prevention is necessary. The orally administered anticancer drug S‐1 contributes to cancer therapy. In a mouse xenograft model of metastatic breast cancer from our previous study, the administration of S‐1 inhibited lung metastasis. However, the mechanism of inhibition remains elusive. S‐1 contains 5‐chloro‐2,4‐dihydroxypyridine (CDHP), which does not have the antigrowth activity, but prevents the degradation of 5‐fluorouracil, an anticancer reagent. In this study, we found that CDHP treatment shrinks cell morphology in metastatic basal‐like breast cancer cell lines. Wound healing assays showed reduced cell migration in CDHP‐treated cells. At the molecular level, CDHP treatment reduced the number of nascent adhesions, whereas the number of mature focal adhesions was not changed. These findings indicate that CDHP impairs focal adhesion formation, which results in a reduction in cell migration. For the in vivo metastasis assay, we used a highly lung‐metastatic cell line. We xenografted them into immunodeficient mice, and administered CDHP. To determine whether CDHP prevents metastasis, we measured the weights of harvested lungs. The results showed that the lung weights of the CDHP‐treated animals were not significantly different compared to the no‐tumor controls, whereas the vehicle group showed a number of metastatic foci and an increase in lung weight. These observations indicate that CDHP administration prevents metastasis. This study reveals a novel effect of CDHP for lung metastasis prevention. Our findings may facilitate the establishment of future metastasis prevention therapies.